The Impact of Covid-19 Pandemic on Interest Rates in Bulgaria - Митева, Дияна (Научни трудове, 2021)
The current paper aims to track the movement of interest rates and volumes for 2020 in Bulgaria. The observed interest rates include those of deposits and loans. As the pandemic caused by Covid-19 started in the beginning of February, 2020 the data used in this paper includes the period January-November 2020. Because of the short period regression analysis is not prepared but comprehensive analysis of large set of data is done.  The main results show that there was a change in deposit and loan market in Bulgaria. The interest rates in the local and euro currency show different volatility as well as the interest rates on households and non-financial corporations deposits. Inflation fell as, did the yield of government debt securities whilst indebtedness in the euro area increases.
Keywords: Пандемия; COVID-19; Лихвени проценти; Депозити; Кредити